MOCHE OCCUPATION IN NORTH MARGIN OF THE LOWEST MOCHE VALLEY, NORTH COAST OF PERU - Gamboa Velásquez, Jorge (2012)
This article discusses the settlements involved in agricultural expansion on the north side of the Moche Valley between the 5th and 8th centuries AD. While the characteristics of the Moche occupation in this area are not completely known, they do yield important data about irrigation systems, road networks, as well residential and monumental architecture. Furthermore, the local material culture, particularly pottery, serves to create a relative chronology of the sector. In this study, which is based on sites survey and excavations in various locations in the Lower Moche Valley, we revise proposals regarding a long-term relation between the north side of the lower valley and processes of political centralization in the area around the Huacas de Moche. Specifically, we focus on the history of a series of communities and ceremonial centers within a landscape that acquired a new role for all of its occupants.